Information and Communication Technologies and Financial Management: A study on Secondary Schools in Greater Bushenyi - Nimusima, Pereez; Tugaineyo, Annah; Kigonya, Lynne; Mugisha, Faith; Rubalema, Alex; Kalinda, Peter; Oceng, Peter; Emmanuel, Erem; Rwakihembo, John (American Journal of Education and Practice, 2023)
Purpose: The financial management of secondary schools is of an unrivalled significance however financial budgeting, monitoring and reporting apparently still remain wanting. The purpose of this study was to examine the relationship between Information and Communication Technologies (ICT) and financial management on Secondary Schools in Greater Bushenyi. Methodology: Mixed methods research design was adopted and collected data at one point in time on 224 repondents who included bursars, headteachers and chairpersons of finance committees of Board of Governors. After collecting data using questionnnaires and interview guides, descriptive and inferential methods of data analysis were used. We were able to present data using tables and verbatim quotes. Findings: The study established that excel spreadsheet is the commonly used software for budgeting and 67% of secondary schools were found to be connected to internet, however, were unfamiliar with the management information systems concepts. The regression results showed that Information Communications Technology has a positive relationship with financial management among schools in Greater Bushenyi. Specifically, findings revealed that availability of financial management soft wares (Beta= .513, P<.01) is a better predictor of financial management and this was followed by internet connectivity (Beta = .433, P<01). However, customised management information system was apparently not a significant predictor of financial management (Beta= .227, P > 01). Such findings mean that if secondary schools allocate sufficient resources towards acquisition of user-friendly financial management soft wares, standby generators, modern computers, constantly upgrade Information and Communications Technology systems, they will be ably prepared to face the rapid changes and growth in technology, and this means that their financial budgeting, planning and reporting will improve. Recommendations: The Information and Communications theory, draws strengths from its emphasis on designing more reliable systems using technology infrastructure which realms well with debate in this study. Since the relationship between ICT and financial management has been confirmed in this study, school administrators are called upon to put much attention on acquiring modern financial management soft wares, and to use relevant information communication technology infrastructure that enable schools to remain internally and externally connected to internet.